PERBANDINGAN STRES AKADEMIK ANTARA MURID YANG MENGIKUTI DAN TIDAK MENGIKUTI EKSTRAKURIKULER PADA MADRASAH ALIYAH NEGERI 2 PADANGSIDIMPUAN PROVINSI SUMATERA UTARA - Alya Rizky; Berto Apriyano; Syahrastani; Nurul Ihsan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the high levels of academic stress experienced by Grade XI students at MAN 2 Padangsidimpuan due to complex academic demands, alongside the hypothesis that participation in extracurricular activities could serve as a stress management mechanism. The study aimed to compare academic stress levels between two categories of Grade XI students at MAN 2 Padangsidimpuan: those involved in extracurricular activities and those who were not. A quantitative approach with a comparative design was employed. The sample consisted of 100 Grade XI students selected via stratified random sampling; of these, 50 were active in extracurricular activities, while the other 50 were not. Data were collected using an academic stress questionnaire comprising 30 Likert-scale statements, with established validity and reliability (Cronbach's Alpha = 0.779). Data analysis was conducted using an Independent Sample t-Test after confirming that the data were normally distributed and exhibited homogeneous variance. The results showed a mean academic stress score of 64.70 for the group participating in extracurricular activities, compared to 78.26 for the non-participating group. With a significance value of 0.000 (below the 0.05 threshold), the t-test confirmed that the difference in academic stress levels between the two groups was statistically significant. These findings indicate that student involvement in extracurricular activities is associated with lower levels of academic stress. The study implies that extracurricular activities serve as a preventive measure for managing academic stress; therefore, it is recommended that schools encourage structured student participation to support their mental health.